A method for evaluating the freeze-thaw durability of ancient blue bricks
By conducting material analysis and antique brick preparation on ancient blue bricks, and using freeze-thaw cycle tests to evaluate the durability of ancient blue bricks, the problem of evaluating the durability of ancient blue bricks in ancient buildings was solved, and effective evaluation and restoration of ancient blue bricks under the freeze-thaw cycle was achieved.
Patent Information
- Application Number
- CN202210831811.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-07-15
AI Technical Summary
The prior art is difficult to be used for durability assessment and service life prediction of ancient blue bricks under freeze-thaw cycle, especially when large-size bricks of standard size cannot be obtained in ancient building structures.
By sampling ancient blue bricks, micro-analysis of the material, antique bricks with similar elements and pore structures to ancient blue bricks were prepared, and freeze-thaw cycle tests were conducted to evaluate the freeze-thaw resistance of ancient blue bricks.
The durability assessment of ancient blue bricks under the freeze-thaw cycle was achieved, which reduced damage to ancient buildings and improved the accuracy of the assessment.
Smart Images

Figure CN115266550B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ancient building restoration, and in particular to a method for evaluating the freeze-thaw resistance durability of ancient blue bricks. Background Art
[0002] Blue bricks occupy an important position in the history of Chinese architecture. Many imperial palaces and royal mansions were built with blue bricks. The ancient blue bricks on these ancient buildings have been damaged to varying degrees over a long period of time. Some of them have even affected the stability of the ancient buildings. Therefore, these ancient blue bricks need to be repaired or replaced. As the concept of ancient building restoration has changed from "repairing the old as it was" to "repairing the old as it was", the requirements for the substitute of ancient blue bricks - antique bricks have also increased accordingly. It is no longer just a requirement for the appearance to be consistent, but also the freeze-thaw resistance and durability of antique bricks must be close to that of ancient blue bricks.
[0003] The testing of the basic properties of existing building bricks is carried out in accordance with the national standard GB / T 5101-2017 "Sintered Ordinary Bricks", which stipulates that the durability evaluation of bricks in freeze-thaw environments is carried out in accordance with GB / T 2542-2012 "Test Methods for Wall Bricks".
[0004] The standard method requires bricks of standard size, requiring 10 pieces. However, since ancient structures cannot be damaged, such large bricks are not available. In-situ sampling of bricks in ancient buildings often yields only small, sporadic samples.
[0005] Therefore, the existing standards are difficult to use for durability assessment and service life prediction of ancient blue brick materials under freeze-thaw cycles, which seriously restricts the progress of durability analysis and repair and reinforcement technology of ancient blue brick building structures. Summary of the Invention
[0006] The purpose of this application is to provide a method for evaluating the freeze-thaw durability of ancient blue bricks, so as to solve the problem that when conducting durability evaluation and service life prediction of ancient blue bricks under freeze-thaw cycles, it is impossible to provide ancient blue brick samples according to the test standards, resulting in the inability to conduct tests and predictions.
[0007] In the first aspect, the present application provides a method for evaluating the freeze-thaw durability of ancient blue bricks, which adopts the following technical solution: A method for evaluating the freeze-thaw durability of ancient blue bricks, comprising the following steps:
[0008] S1. Sampling of ancient blue bricks
[0009] Obtain ancient blue brick samples from the blue brick masonry structure to be tested;
[0010] S2. Analysis of Ancient Blue Brick Materials
[0011] The element composition and pore structure distribution of the ancient blue brick material in S1 were obtained using the material microanalysis method;
[0012] S3. Antique brick preparation
[0013] Using a similar reduction method, antique brick specimens with similar element composition and pore structure to the ancient blue brick samples were prepared.
[0014] S4. Antique tile similarity verification
[0015] Use the material microscopic analysis method to verify the similarity between the antique brick specimen in S3 and the ancient blue brick in S1. If the similarity is above 85%, proceed to the next step; if the similarity is insufficient, repeat S3;
[0016] S5. Freeze-thaw cycle test
[0017] The antique brick specimens in S4 with a similarity of more than 85% were used to conduct freeze-thaw cycle tests, and the durability of the ancient blue bricks in S1 under freeze-thaw cycles was evaluated based on the test results.
[0018] By adopting the above technical solution, a small number of smaller-sized ancient blue bricks are used, and the ancient blue bricks are measured and analyzed according to the material microanalysis method, and a number of standard-sized antique bricks are prepared based on the results; antique bricks with a similarity to the ancient blue bricks higher than 85% are selected as samples, and freeze-thaw cycle tests are carried out, and the durability of the ancient blue bricks in S1 under freeze-thaw cycles is evaluated based on the test results; thereby, the durability of the ancient blue bricks under freeze-thaw cycles can be evaluated using a small number of non-standard-sized ancient blue bricks.
[0019] Optionally, in S2, the porosity and pore distribution of the ancient blue bricks are obtained by mercury intrusion porosimetry.
[0020] By adopting the above technical solution, the porosity and void distribution of the ancient blue brick can be obtained by the mercury intrusion method; thereby providing a theoretical basis on the microstructure for the preparation of antique bricks, and when the antique bricks are screened in the later stage, antique bricks with porosity and pore distribution similar to those of the ancient blue bricks can be screened out, thereby improving the accuracy of evaluating the durability of the ancient blue bricks through the antique bricks.
[0021] Optionally, in S2, SEM combined with EDX method is used to observe the regional microscopic appearance of the ancient blue bricks and the types and contents of elements in the area.
[0022] By adopting the above technical scheme, a theoretical basis for the micromorphology of the preparation of antique bricks is provided, and the prepared antique bricks are compared with ancient blue bricks in micromorphology. Antique bricks with micromorphology similar to ancient blue bricks are selected for testing, thereby improving the accuracy of evaluating the durability of ancient blue bricks through antique bricks.
[0023] Optionally, in S2, the XRF method is used to measure the element types and element contents of the entire ancient blue brick sample.
[0024] By adopting the above technical solution, the element types and element contents of the entire ancient blue brick sample are measured, providing a theoretical basis for the overall element types and content composition of antique bricks. In addition, this method can be used to screen out antique bricks that are closer to the ancient blue bricks in terms of overall element types and content composition when selecting antique bricks, thereby improving the accuracy of evaluating the durability of ancient blue bricks through antique bricks.
[0025] Optionally, before measuring the ancient blue brick sample using the XRF method, the sample is first ground for two hours and passed through a 200-mesh sieve.
[0026] By adopting the above technical solution, the diameter of the sample particles can be reduced, the error can be reduced, and the measurement accuracy can be improved.
[0027] Optionally, in S4, the material microscopic analysis method used is the same as that in S2.
[0028] Optionally, in S5, the freeze-thaw cycle test includes the following steps:
[0029] S5.1 Saturated water freeze-thaw cycle test
[0030] Take several antique brick specimens, divide them into eight groups, and conduct freeze-thaw cycle tests for 10, 20, 30, 40, 50, 60, 70 and 80 times respectively, and record the mass loss rate of the specimens after the test;
[0031] S5.2 Freeze-thaw cycle test at different water saturations
[0032] Take several specimens and group them into groups according to their water saturation to conduct freeze-thaw cycle tests; and measure the mechanical properties of the specimens after the test.
[0033] By adopting the above technical scheme, the mass loss rate of saturated antique bricks under different freeze-thaw cycles and the mechanical properties of antique bricks with different saturations under freeze-thaw cycle tests are measured, so as to comprehensively evaluate the durability of antique bricks. The selected antique brick samples are similar to those of ancient blue bricks in microstructure, element composition and content. Therefore, the freeze-thaw durability of ancient blue bricks can be evaluated by measuring the data of antique bricks under freeze-thaw cycle tests.
[0034] Optionally, in the freeze-thaw cycle test with different water saturations in 5.2, the water saturations of the specimens are divided into three groups, and the water saturations of each group are 0.9 / 0.95 and 1, respectively.
[0035] By adopting the above technical solution, freeze-thaw cycle tests are carried out on samples with different water saturations, thereby simulating the performance of samples in different environments during freeze-thaw tests, thereby evaluating the durability of ancient blue bricks in different environments and improving the applicability and accuracy of the durability evaluation of ancient blue bricks.
[0036] Optionally, in the freeze-thaw cycle test at different water saturations in 5.2, the mechanical property measurement includes measurement of compressive strength and relative dynamic elastic modulus.
[0037] By adopting the above technical solution, compressive strength and relative dynamic elastic modulus are two mechanical properties that have a greater impact on the durability of ancient blue bricks, and are easy to measure in experiments, which can improve the accuracy of the durability evaluation of ancient blue bricks.
[0038] In the second aspect, the present application provides an antique brick adopting the following technical solution:
[0039] An antique brick is produced by using S1-S4 of the above-mentioned method for evaluating the freeze-thaw resistance durability of the ancient blue brick.
[0040] By adopting the above technical solution, the prepared ancient blue bricks can be used to repair ancient buildings.
[0041] In summary, this application includes at least one of the following beneficial technical effects:
[0042] 1. This application uses a small amount of small-sized ancient blue bricks to imitate ancient blue bricks, thereby obtaining antique bricks with similar performance and microstructure to ancient blue bricks. Freeze-thaw tests are conducted on the antique bricks, and the durability of the ancient blue bricks is evaluated based on the test data. The amount and size of the ancient blue bricks used will cause minimal damage to the ancient buildings. In addition, ancient blue bricks that have fallen off the ancient buildings can be used, thereby achieving the purpose of evaluating the durability of the ancient blue bricks while reducing damage to the ancient buildings.
[0043] 2. Through the microscopic analysis of the materials of ancient blue bricks, and using the data obtained from the analysis to imitate the ancient blue bricks, antique bricks are obtained, and then the obtained antique bricks are analyzed. Antique bricks with a high degree of similarity to ancient blue bricks are selected as samples for the durability evaluation of ancient blue bricks, thereby improving the accuracy of the durability evaluation of ancient blue bricks through antique bricks. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 1 is a flow chart of a method for evaluating the freeze-thaw resistance durability of ancient blue bricks described in an embodiment of the present application;
[0045] Figure 2 Schematic diagram of the test results of the ancient blue brick mercury injection method described in the examples of the present application;
[0046] Figure 3This is a 5100x scanning electron microscope image of the ancient blue brick 3 described in the embodiment of the present application;
[0047] Figure 4 This is a 20,000x scanning electron microscope image of the ancient blue brick 3 described in the embodiment of the present application;
[0048] Figure 5 This is a schematic diagram of the position of the detection area of the ancient blue brick 3 by the EDX energy spectrum described in the embodiment of the present application;
[0049] Figure 6 This is the EDX analysis result of the detection area of the ancient blue brick 3 described in the embodiment of the present application;
[0050] Figure 7 is a graph showing the pore volume change versus pore diameter for antique bricks and ancient blue bricks in the examples of the present application;
[0051] Figure 8 This is a 5100x scanning electron microscope image of the antique brick 1 described in the embodiment of the present application;
[0052] Figure 9 This is a 20,000x scanning electron microscope image of the antique brick 1 described in the embodiment of the present application;
[0053] Figure 10 This is a schematic diagram of the detection area position of the antique brick 1 by the EDX energy spectrum described in the embodiment of the present application;
[0054] Figure 11 This is the EDX analysis result of the detection area of the antique tile 1 described in the embodiment of the present application.
[0055] Figure 12 This is a mass loss rate curve of the antique brick in the embodiment of the present application subjected to a saturated water freeze-thaw cycle test;
[0056] Figure 13 This is a picture of the appearance of the antique brick after 10 freeze-thaw tests as described in the examples of this application;
[0057] Figure 14 This is a picture of the appearance of the antique brick after 20 freeze-thaw tests in the examples of this application;
[0058] Figure 15 This is a picture of the appearance of the antique brick after 30 freeze-thaw tests in the embodiment of the present application;
[0059] Figure 16 This is a picture of the appearance of the antique brick after 40 freeze-thaw tests in the examples of this application;
[0060] Figure 17 This is a picture of the appearance of the antique brick after 50 freeze-thaw tests in the embodiment of the present application;
[0061] Figure 18This is a picture of the appearance of the antique brick after 60 freeze-thaw tests in the embodiment of the present application;
[0062] Figure 19 This is a picture of the appearance of the antique brick after 70 freeze-thaw tests in the embodiment of the present application;
[0063] Figure 20 This is a picture of the appearance of the antique brick after 80 freeze-thaw tests in the embodiment of the present application;
[0064] Figure 21 This is a curve showing the compressive strength change of antique bricks with different water saturations under different freeze-thaw cycle test times in the embodiment of the present application.
[0065] Figure 22 This is a curve showing the change in relative dynamic elastic modulus of antique tiles with different water saturations under different freeze-thaw cycle test times in the embodiments of the present application. DETAILED DESCRIPTION
[0066] The following is combined with Figure 1 -Attached Figure 22 , further details of this application are given.
[0067] A method for evaluating the freeze-thaw durability of ancient blue bricks, referring to Figure 1 , including the following steps:
[0068] S1. Sampling of ancient blue bricks
[0069] Obtain ancient blue brick samples from the blue brick masonry structure to be tested;
[0070] S2. Analysis of Ancient Blue Brick Materials
[0071] The element composition and pore structure distribution of the ancient blue brick material in S1 were obtained using the material microanalysis method;
[0072] S3. Antique brick preparation
[0073] Using a similar reduction method, antique brick specimens with similar element composition and pore structure to the ancient blue brick samples were prepared.
[0074] S4. Antique tile similarity verification
[0075] Use the material microscopic analysis method to verify the similarity between the antique brick specimen in S3 and the ancient blue brick in S1. If the similarity is above 85%, proceed to the next step; if the similarity is insufficient, repeat S3;
[0076] S5. Freeze-thaw cycle test
[0077] The antique brick specimens in S4 with a similarity of more than 85% were used to conduct freeze-thaw cycle tests, and the durability of the ancient blue bricks in S1 under freeze-thaw cycles was evaluated based on the test results.
[0078] Example
[0079] A method for evaluating the freeze-thaw durability of ancient blue bricks comprises the following steps: first, collecting approximately 50 g of in-situ ancient blue brick material from an existing ancient building with blue brick masonry structure, and labeling them as ancient blue brick 1, ancient blue brick 2, and ancient blue brick 3 (the ancient blue brick material used in this embodiment comes from Beijing, and the raw materials for the antique bricks described below come from Renqiu City, Hebei Province).
[0080] A piece of the larger ancient blue brick 3 was broken off with pliers and placed in the AutoPoreⅣ9500 fully automatic mercury intrusion instrument for testing. The pore size measurement range is 4nm-360μm. The pore structure was measured using the mercury intrusion method. The results are as follows: Figure 2 shown.
[0081] Mercury intrusion porosimetry is used here to analyze the porosity and pore distribution of porous material structures. CT can also be used, but CT is more expensive.
[0082] The Phenom XL scanning electron microscope was used to test the ancient blue brick 3. The microstructure of the sample was observed by SEM, such as Figure 3 As shown, this is a scanning electron microscope image of the ancient blue brick 3 at 5100 times. Figure 4 Shown is a scanning electron microscope image of the ancient blue brick 3 at 20,000 times magnification.
[0083] The EDX spectrum is used to detect the types and contents of the elements in the micro-region of the sample, specifically Figure 5 Mark the area and determine the basic element composition of the material in this area, such as Figure 6 The statistical results are shown in Table 1 below:
[0084]
[0085] Table 1 Types and contents of elements in the ancient blue brick region
[0086] For microstructure morphology, optical microscopes can also be used, but optical microscopes have low magnification and short depth of field. For micro-region composition, EPMA (electron probe microanalyzer) can also be used.
[0087] The above-mentioned ancient blue bricks 1, 2, and 3 were ground for two hours respectively and passed through a 200-mesh sieve. Sufficient powder was taken and sent to a fluorescence analyzer (Bruker S8 TIGER Series 2 XRF fluorescence analyzer was selected). The following results were obtained:
[0088]
[0089] Table 2 Main element content of ancient blue bricks (%)
[0090] XRF is commonly used for elemental determination in samples. XRF can quickly and accurately identify the corresponding element type and perform quantitative analysis based on the relationship between the intensity of fluorescent X-rays and the corresponding element content.
[0091] In addition, there is pXRF (portable X-ray fluorescence spectrometry), but the lack of data accuracy of pXRF is a key issue and needs to be corrected in combination with laboratory test data.
[0092] Other commonly used elemental analysis techniques include AAS (atomic absorption spectrometry), ICP-AES (inductively coupled plasma atomic emission spectrometry), ICP-MS (inductively coupled plasma mass spectrometry), XPS (X-ray photoelectron spectroscopy), etc.
[0093] The elemental analysis results of the samples reflect the overall and macroscopic characteristics of the element types and content of the samples.
[0094] The results of micro-area element analysis reflect the element types and content characteristics of a certain tiny area of the sample.
[0095] The different elemental compositions and percentages within a material determine its properties and uses, and can also be used to infer the origin of green bricks. In the raw soil, Si significantly influences the strength of the fired brick; Al content determines the compressive strength of the fired brick; Ca acts as a glass phase during the sintering process, lowering the sintering temperature; and Fe determines the color of the fired brick and reduces the raw material's refractoriness.
[0096] The microstructure of a material plays a decisive role in its mechanical properties. It determines the stress-strain state caused by the load and controls its macroscopic mechanical response and failure mechanism. For example, under the action of freeze-thaw cycles, water freezes in the pores of the material, causing pore expansion and cracking, which changes the microstructure of the material, thereby significantly reducing the material's elastic modulus, compressive strength, tensile strength and other mechanical properties.
[0097] (1) Elemental analysis of samples is used to reflect the overall macroscopic properties of the blue brick samples and to infer the origin of the samples.
[0098] (2) Micro-area element analysis is used to compare the similarity between antique bricks and antique-style new bricks in detail. By detecting and comparing the elements in the similar microstructural areas of the two bricks, the similarity of the chemical and mechanical properties of the two samples can be comprehensively reflected.
[0099] When the similarity of the antique brick reaches more than 85% of the ancient blue brick, it can be judged that the performance of the antique brick is similar to that of the ancient blue brick.
[0100] Use "relative error Er" to evaluate the similarity between antique tiles and ancient tiles, and ensure that the relative error is no more than 15%.
[0101]
[0102] (X antique brick is the content of the main elements of the antique brick sample as a whole, and X ancient brick is the average content of the main elements of the ancient blue brick sample as a whole).
[0103] The above data is then taken to a brick factory for the production of antique-style bricks. The process includes raw material processing, blank making, drying, and firing. The element types and content are determined by the selection of raw material soil, while porosity is primarily achieved through sintering temperature control, slurry clarification, and clay preparation. The detailed process flow, based on the requirements for producing antique-style blue bricks, is described below.
[0104] 1.1 Raw material processing
[0105] (1) Soil selection
[0106] XRF element analysis was performed on the raw soil to ensure that the content of the main elements was no less than 85% similar to that of the ancient blue brick samples.
[0107] (2) Aging: After the raw soil is removed, it is piled in an open area to form a large pile for aging. Water is sprayed regularly to keep the pile moist. The aging process generally takes one to three years. Aging helps to enhance the plasticity of the raw soil, making the processed bricks less likely to dry out and crack.
[0108] (3) Clarifying the pulp
[0109] The aged soil is simply crushed and sieved, then placed in a pool of water to soak and settle, and the fine-grained soil in the middle layer on the bottom of the pool is taken out.
[0110] (4) Clay preparation
[0111] Put the fine-grained mud that has been clarified into a slurry into a blender and stir it. When stirring, be sure to add water to keep the mud moist.
[0112] 1.2 Blanking
[0113] Pour the clay into the mold made of wood board with force. The amount of clay should be slightly more than the volume of the mold. The excess part should be hung off and the surface should be smoothed. Then turn the mold filled with clay upside down on the flat ground covered with fine sand. There should be gaps between the bricks to facilitate ventilation and drying.
[0114] 1.3 Drying
[0115] Lay the bricks flat to dry for a day, then stand them up and dry them for another half a day.
[0116] After drying, use wooden boards to beat the vertical surfaces of the bricks to make them flat.
[0117] Place the bricks neatly in a cool place, leaving gaps between them for ventilation and shade drying. The shade drying time is about half a month.
[0118] 1.4 Calcination
[0119] The kiln firing process uses biomass fuels such as rice husks, firewood, straw, and rice straw. The kiln firing process takes 15 to 20 days, depending on the number of bricks. The most important thing during the kiln firing process is to control the temperature according to the degree of burnt bricks.
[0120] (1) Kiln firing
[0121] ① Ignition: Ignite the closed brick kiln filled with bricks. Place a layer of flammable straw on the grate at the bottom of the kiln as fire starter. After ignition, gradually add some rice husks and straw until a thick layer of ash and charcoal with sparks accumulates on the grate.
[0122] ② Firing: The kiln temperature is raised from room temperature to approximately 600°C. To prevent the bricks from dehydrating rapidly, shrinking rapidly, and cracking, the kiln temperature is raised slowly. Straw is added approximately every 10 minutes to ensure the fire continues. Ventilation and moisture removal are also enhanced. Once the white smoke has been exhausted and the bricks have a reddish hue, the next step can be carried out.
[0123] ③ Firing: Raise the kiln temperature from 600°C to around 900°C. Raise the temperature slowly and steadily, ensuring adequate airflow. Add fuel in small, frequent additions to ensure complete combustion. Maintain the temperature at around 900°C, controlling ventilation appropriately. When the bricks reach a purple-red color, proceed to the next step.
[0124] ④ Twist the smoke. The kiln temperature rises from 900°C to around 1000°C. Key points to this operation include frequent fuel addition, large fuel masses, reduced ventilation, minimal ash removal, and a continuous fire with black smoke production. After three to four days, remove the bricks from the deep and place them in water. If the cross-section turns blue, stop the fire and proceed to the next step.
[0125] (2) Wetting kiln
[0126] First, seal all openings in the kiln. Cover the chimney with a cover plate, then cover it with a layer of soil and tamp it down to make the kiln airtight. The water seepage time is about 5 days.
[0127] Three pieces are randomly selected from the qualified antique bricks (here referring to the qualified antique bricks produced by the brick factory according to the standard production process) and are marked as antique brick 1, antique brick 2 and antique brick 3 respectively.
[0128] A small piece of material was taken from antique brick 1, and the porosity and pore distribution were measured by mercury intrusion method. The mercury intrusion test used AutoPoreⅣ9500 fully automatic mercury intrusion instrument with a pore size measurement range of 4nm-360μm. The results are as follows: Figure 7 shown; from Figure 7It can be seen that the porosity and pore size distribution of antique bricks and ancient blue bricks are very similar, but the pore sizes of the two are slightly different, with the pore size of antique bricks ranging from 20nm to 5μm, and the pore size of ancient blue bricks ranging from 20nm to 7μm. This may be because the in-situ blue bricks of ancient buildings have been affected by freeze-thaw damage and other erosion during long-term service, causing the larger pores to expand and crack due to the frost heave force, resulting in larger pores.
[0129] The antique brick 1 was tested using a Phenom XL scanning electron microscope. The micromorphology of the sample was observed by SEM, such as Figure 8 As shown, it is a scanning electron microscope image of antique brick 1 at 5100 times. Figure 9 Shown is a scanning electron microscope image of the antique brick 1 at 20,000 times.
[0130] By comparison Figure 3 、 Figure 4 and Figure 8 、 Figure 9 ; From the SEM images, it can be seen that the antique bricks and ancient blue bricks are consistent in microscopic morphology, both showing a porous, loose block structure. This microstructure corresponds to the higher water absorption rate of blue bricks on a macro scale.
[0131] The EDX spectrum is used to detect the types and contents of the elements in the micro-region of the sample, specifically Figure 10 Mark the area and determine the basic element composition of the material in this area, such as Figure 11 The statistical results are shown in the following table:
[0132]
[0133] Table 3 Types and contents of elements in antique brick regions (%)
[0134] The above-mentioned antique bricks 1, 2 and 3 were ground for two hours respectively and passed through a 200-mesh sieve. Sufficient powder was taken and sent to a fluorescence analyzer (Bruker S8 TIGER Series 2 XRF fluorescence analyzer was selected). The following results were obtained:
[0135]
[0136] Table 4 Main element types and contents of antique tiles (%)
[0137]
[0138]
[0139] Table 5 Relative error (%) of the main elements and contents of antique bricks compared with ancient blue bricks
[0140] As can be seen from Table 5, the errors between the elements of antique bricks and the mean values of ancient blue bricks are all within 15%, that is, the similarity reaches more than 85%.
[0141] By comparing and analyzing the SEM-EDX results of ancient blue bricks ( Figure 5 、 Figure 6 , Table 1) and antique brick results ( Figure 10 、 Figure 11 , Table 3), the main components of antique bricks and ancient blue bricks are O, Si and Al, which is consistent with the XRF analysis results. Combined with the element content analysis, it can be further determined that they are mainly composed of SiO2 and Al2O3, and the Si content is higher than the Al content; both bricks contain a small amount of Fe, but overall the Fe content of antique bricks is higher than that of ancient blue bricks; in addition, both bricks contain trace elements such as K, Ca, Mg, Na, S, and ancient blue bricks contain a small amount of N.
[0142] The above microscopic test results show that, whether it is SEM microscopic analysis, EDX and XRF elemental analysis, or mercury intrusion pore structure analysis, antique bricks and ancient blue bricks are generally very similar, with little difference between the two. Therefore, whether it is using antique bricks instead of ancient blue bricks for scientific research or using antique bricks instead of ancient blue bricks for ancient building restoration, the above test results can provide certain theoretical support.
[0143] 8 groups of 24 pieces (3 pieces / group) of the antique bricks prepared above were selected, and the antique bricks were subjected to a saturated freeze-thaw cycle test; the freeze-thaw cycle tests were carried out 10 times, 20 times, 30 times, 40 times, 50 times, 60 times, 70 times and 80 times, and the mass of the antique bricks was recorded after every ten freeze-thaw cycle tests, and the mass loss rate of the antique bricks was calculated, as shown in FIG. Figure 12 As shown; and record the appearance pictures, such as Figures 13-20 shown.
[0144] 120 pieces of the antique bricks prepared above were selected for freeze-thaw cycle tests with different water saturations. Two groups were tested for each test condition, with three specimens in one group. This freeze-thaw cycle test included three water saturations: 0.9 / 0.95 / 1;
[0145] The antique bricks with a saturation of 1 were subjected to freeze-thaw cycle tests for 10 / 20 / 30 / 40 / 50 / 60 / 70 / 80 times respectively, and the compressive strength and relative dynamic elastic modulus of the antique bricks after the freeze-thaw cycle tests were recorded;
[0146] The antique tiles with a saturation of 0.95 were subjected to 20 / 40 / 60 / 80 freeze-thaw cycle tests, and the compressive strength and relative dynamic elastic modulus of the antique tiles after the freeze-thaw cycle tests were recorded;
[0147] The antique tiles with a saturation of 0.9 were subjected to freeze-thaw cycle tests for 10 / 20 / 30 / 40 / 50 / 60 / 70 / 80 times, and the compressive strength and relative dynamic elastic modulus of the antique tiles after the freeze-thaw cycle tests were recorded;
[0148] The curves of the compressive strength of the above three groups of antique bricks with different saturation as the number of freeze-thaw tests increases are as follows: Figure 21 As shown; the change curve of relative dynamic elastic modulus is shown in Figure 22 shown.
[0149] Based on the above test results on changes in compressive strength, relative dynamic elastic modulus, and porosity, we can analyze that the porosity of antique tiles is approximately 27%-33%. When the water saturation is not 1, the damage of antique tiles continues to increase during the first 40 freeze-thaw cycles, and then tends to be flat after 40 cycles. Moreover, under the same number of freeze-thaw cycles, the freeze-thaw cycle damage increases with increasing water saturation. Overall, the three indicators of change in compressive strength, relative dynamic elastic modulus, and porosity correspond to each other.
[0150] From this case, it can be determined that by confirming that the microscopic properties of antique bricks are consistent with those of the original ancient building blue bricks, the freeze-thaw cycle test results of antique bricks can be used to predict the degradation process of ancient building blue brick materials under freeze-thaw cycle conditions, thereby completing the durability assessment goal of ancient building blue brick materials.
[0151] The examples of this specific embodiment are all preferred embodiments of this application and are not intended to limit the scope of protection of this application. Identical components are represented by the same reference numerals. Therefore, any equivalent changes made based on the structure, shape, and principle of this application should be included in the scope of protection of this application.
Claims
1. A method for evaluating the freeze-thaw durability of ancient blue bricks, characterized in that: The following steps are involved: S1. Sampling of ancient blue bricks Obtain ancient blue brick samples from the blue brick masonry structure to be tested; S2. Analysis of ancient blue brick materials Using the material microanalysis method, the element composition and pore structure distribution of the ancient blue brick material in S1 were obtained; S3. Antique brick preparation The similar reduction method was used to prepare antique brick specimens with similar element composition and pore structure as the ancient blue brick samples. The specific process flow was as follows: raw material processing, blank making, blank drying and baking. Among them, the raw material processing includes: soil selection, aging, slurry clarification and mud kneading. When selecting soil, the raw material soil is subjected to XRF element analysis to ensure that the content of the main elements is not less than 85% similar to that of the ancient blue brick sample; S4. Antique brick similarity verification Use the material microscopic analysis method to verify the similarity between the antique brick specimens in S3 and the ancient blue bricks in S1, and use the "relative error Er" to evaluate the similarity between the antique bricks and the ancient bricks, ensuring that the relative error is no more than 15%. Among them, X antique brick is the content of each main element of the antique brick sample as a whole, and X ancient brick is the average content of each main element of the ancient blue brick sample as a whole. If the similarity is above 85%, proceed to the next step; if the similarity is insufficient, repeat S3; S5. Freeze-thaw cycle test The antique brick specimens in S4 with a similarity of more than 85% were used to carry out freeze-thaw cycle tests, and the durability of the antique blue bricks in S1 under freeze-thaw cycles was evaluated based on the test results.
2. The freeze-thaw durability evaluation method of ancient blue bricks according to claim 1, characterized in that: In S2, the porosity and pore distribution of the ancient blue brick are obtained by mercury injection method.
3. The freeze-thaw durability evaluation method of ancient blue bricks according to claim 1, characterized in that: In S2, SEM combined with EDX method was used to observe the regional microscopic appearance of the ancient blue bricks and the types and contents of elements in the area.
4. The freeze-thaw durability evaluation method of ancient blue bricks according to claim 1, characterized in that: In S2, the XRF method is used to measure the element types and element contents of the entire ancient blue brick sample.
5. The freeze-thaw durability evaluation method of ancient blue bricks according to claim 4, characterized in that: Before measuring the ancient blue brick samples using the XRF method, the samples were ground for two hours and passed through a 200-mesh sieve.
6. The freeze-thaw durability evaluation method of ancient blue bricks according to any one of claims 1 to 4, characterized in that: In S4, the material microscopic analysis method used is the same as that in S2.
7. The freeze-thaw durability evaluation method of ancient blue bricks according to claim 1, characterized in that: In S5, the freeze-thaw cycle test comprises the following steps: S5.1 Saturated freeze-thaw cycle test Take several antique brick specimens and divide them into eight groups. Perform freeze-thaw cycle tests for 10, 20, 30, 40, 50, 60, 70 and 80 times respectively. Record the mass loss rate of the specimens after the test. S5.2 Freeze-thaw cycle test at different water saturation Take several specimens and group them into groups according to different water saturation levels for freeze-thaw cycle tests; and measure the mechanical properties of the specimens after the test.
8. The freeze-thaw durability evaluation method of ancient blue bricks according to claim 7, characterized in that: In the freeze-thaw cycle test with different saturations in 5.2, the saturations of the specimens are divided into three groups, and the saturations of the groups are 0.9 / 0.95 and 1 respectively.
9. The freeze-thaw durability evaluation method of ancient blue bricks according to claim 7, characterized in that: In the freeze-thaw cycle test at different water saturation levels in 5.2, the mechanical property measurement includes the measurement of compressive strength and relative dynamic elastic modulus.
10. An antique brick, characterized in that: The method is prepared by using S1-S4 in the freeze-thaw durability evaluation method of the ancient blue brick described in claim 1.
Citation Information
Patent Citations
Determination method for weatherability of ancient masonry building
CN105092455A
Fly ash archaized black brick
CN106278078A